Predictor Factors of Female Sexual Distress in a Population-Based Sample of Iranian Women: a Path Analysis: Predictors of Female Sexual Distress - Bayat, Fatemeh; Ozgoli, Giti; Mahmoodi, Zohreh; Nasiri, Malihe (Urology Journal, 2023)
Purpose: To investigate the direct and indirect effects of demographic characteristics, relationship satisfaction, and psychological factors on female sexual distress (FSD) using path analysis. Materials and Methods: This study was conducted in two stages. Initially we obtained the FSD predictor factor's conceptual model through a literature review and expert panel. In the Second stage, a population-based cross-sectional study on 207 non-pregnant and married women (without any age restriction) in Zanjan, Iran was conducted. FSDs-R, FSFI-6, DASS-21, and GEMREL Standard questionnaires and the demographic researcher-made questionnaire were used in this study. The data undergone path analysis based on the initial conceptual model. Results: Sexual function (SF) had the strongest relationship with FSD from the direct path (β = -.49) and overall effect (β = -.58). The highest indirect effect belonged to depression-anxiety-stress level (β = .284) mediated by SF (β = -.42) and relationships satisfaction with spouse (β = -.20). Age difference (β = -.13) and relationships satisfaction with spouse (β = -.19) had only a direct effect on FSD. Marriage Duration had only indirect effect on FSD through mediating role on SF (β = -.26) and depression-anxiety-stress level (β = -.15). Conclusion: Among the predictor factors investigated in this study, sexual dysfunction is the most important predictor of FSD. In addition; men older than their spouses, longer marriage duration, relationship dissatisfaction with the spouse and higher rate of depression-anxiety-stress have positive correlation with SD. Therefore, we should offer a combination of the mentioned factors in providing care for women with SD.